PENGARUH DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI PT ALAM JAYA GRAHA - Abdullah, Aliah; Army, Widya Lelisa; Rahayu, Tutik (Jurnal EBI, 2024)
Work discipline is a crucial factor in achieving a company's goals. This study aims to determine the impact of work discipline on employee performance in the Logistics Division of PT Alam Jaya Graha. The company operates in the transportation sector and is based in Bekasi, West Java. The research was conducted using arithmetic mean and simple linear regression methods, with a sample size of 71 respondents and census is adapted. The findings indicate that the average work discipline score is 3.55, which falls into the "Good" category, and the average employee performance score is 3.56, also categorized as "Good." Furthermore, the simple linear regression analysis shows that work discipline has a positive and significant effect on employee performance (0.00 0.05). The coefficient of determination obtained is 97%, indicating that work discipline has a substantial contribution to influencing employee performance. Future research is recommended to use different methods and a combination of more independent variables